Konstruksi Semiotik Representasi PTSD pada Karakter Janiyah dalam Film Straw (2025) - Safira Dwi Apriyani; Rocky Prasetyo Jati (CV. ITTC INDONESIA, 2026)
Post-Traumatic Stress Disorder (PTSD) is increasingly depicted in global cinema, yet its semiotic construction in film remains underexplored in academic discourse. This article aims to examine the semiotic construction of PTSD symptoms represented through the character of Janiyah in the film Straw (2025) and to reveal the social critique embedded in the film regarding mental health stigma. This study employs a qualitative approach using Roland Barthes' semiotic analysis consisting of three levels of meaning: denotation, connotation, and myth. Data were collected through non-participatory observation of six key scenes presenting dialogues, facial expressions, gestures, and visual signs related to Janiyah's psychological condition, analyzed using the Miles and Huberman (2013) model. The findings show that Straw represents three major symptoms of PTSD: hyperarousal, avoidance, and re-experiencing. At the denotative level, the film depicts Janiyah as confused, defensive, emotionally unstable, and hallucinatory toward her deceased child. At the connotative level, these signs reveal unresolved grief, dissociation, social isolation, and an inability to accept reality. At the level of myth, the film criticizes the stigma surrounding mental health and the social construction that expects mothers to remain strong and resilient under any circumstances. Therefore, Straw functions not only as entertainment but also as a form of mass communication that represents psychological trauma and encourages public awareness of mental health.